The Effects of Polypropylene Fibres on the Shear Behaviour of a Concrete Crack: An Experimental Study - Francisco Ortiz-Navas; Juan Navarro-Gregori; Pedro Serna (Fibers, 2025)
The objective of this study is to investigate the effects of macrosynthetic polypropylene fibres as shear reinforcement in a concrete crack. An experimental study was conducted using twenty push-off specimens with varying volumes of fibres, along with plain concrete specimens as a reference. The testing methodology allowed for the analysis of crack kinematics by measuring the evolution of normal and shear stresses in relation to slip and crack opening. This facilitated the creation of diagrams similar to those presented by Walraven (1980) for crack interface shear transfer, but in this case, applied to concrete reinforced with macrosynthetic polypropylene fibres. The findings demonstrate that macrosynthetic polypropylene fibres significantly enhance shear behaviour, particularly when their volume exceeds 8 kg/m3. This study provides valuable insights into the behaviour of macrosynthetic polypropylene fibres under shear loading conditions and highlights their potential benefits as effective shear reinforcement.